El Juzgamiento de Miembros de Comunidades, Pueblos y Nacionalidades Indígenas bajo los Principios de Plurinacionalidad e Interculturalidad, en Compatibilidad con los Preceptos de la Sentencia 112-14-JH/21 de la Corte Constitucional - Huilca Cruz, Marjorie Elizabeth (2022)
This article deals with the prosecution of members of indigenous communities, peoples or nationalities by ordinary justice, either because they are under its jurisdiction or because the indigenous jurisdiction has decided not to act, within the framework of the principles of plurinationality and interculturality. recognized by the Constitution of the Republic of Ecuador of 2008. The main objective is to establish the method and principles that must be applied by ordinary justice, throughout a process, when the member of an original people is involved. . It was also proposed as objectives to identify the jurisprudential line developed by the Constitutional Court regarding indigenous jurisdiction; and, analyze the sentences issued by the Constitutional Court, which refer to indigenous justice and intercultural interpretation. In order to meet the established objectives, a documentary investigation was used and a qualitative methodology was applied, cohort case analysis, since Judgment 112-14-JH/21 was analyzed, as well as other jurisdictional decisions of the Constitutional Court that They deal with issues related to the recognition of indigenous jurisdiction. The main results that could be identified when carrying out this work is that, from the recognition of the Ecuadorian State as plurinational and intercultural in the 2008 Constitution, there are multiple decisions issued by the Constitutional Court regarding indigenous justice; and, in addition, it was possible to demonstrate that the Constitutional Court, through its decisions, guarantees indigenous communities, peoples and nationalities, the right to create, develop and apply their own law according to their customs. Finally, it was verified that the Constitutional Court in Judgment 112-14-JH/21, has expressly established that, for the effective protection of the rights of indigenous communities, peoples and nationalities, an intercultural interpretation is essential, both of rights as well as constitutional guarantees, during the conduct of a judicial process.